(untitled) (Nigerian Journal of Technology, 2024)
Even with pre-drilling geophysical surveys, the failure rates and suboptimal productivity of some boreholes within the University of Ilorin (UNILORIN) are a cause for concern. This present study investigated the hydrogeological capability and potentiality of some borehole sites at the university. To achieve this, an inventory of 47 boreholes with an existing lineament density map and Groundwater Potential Zonation (GWPZ) map of Ilorin South Local Government Area were integrated. These boreholes were categorized based on the lineament density, and groundwater potentiality. The results showed that 96% of the sampled boreholes were sited on zones of low groundwater potential (LGWP) while 4% were on zones of moderate groundwater potential (MGWP). Also, 17% of the boreholes coincided with zones of moderate lineament density, 83% of boreholes coincided with zones of low lineament density and no borehole was found to coincide within areas of high lineament density. The findings suggested that 83% of these boreholes (39 units) were drilled due to exigencies (e.g., cost consideration, proximity to facilities etc.) while only 17% of these boreholes (8 units) were drilled on account of scientific necessity or after the appropriate geoscientific evaluation was done. The findings in this study will benefit stakeholders and practitioners in water resource management in building robust model and database at both regional and local levels.